PENENTUAN FREKUENSI PEMBERIAN PAKAN UNTUK MENDUKUNG PERTUMBUHAN BENIH IKAN PATIN PASUPATI [Determination of Different Feeding Frequency on The Growth of Patin Pasupati Fingerlings] - Evi Tahapari; Ningrum Suhenda (BERITA BIOLOGI, 2009)
The feeding rate and the feeding frequency influencing the growth and survival rate of fish. The objective of this research was to know the proper level of feeding frequency for supporting the growth of patin pasupati (hybride between Pangasius hyphophthalmus and P. djambal).The experiment was conducted in fibre glass tanks located at Research Instalation for Genetic and Freshwater Aquaculture Technology, Sukamandi. Patin pasupati fingerling with average body weight of 2.23 Â± 0.48 g were stocked in 9 fibre glass tanks, each filled with 30 litres of water.The experimental design was Completely Randomized Design with 3 treatments and 3 replications. The treatments were feeding frequency as follows 1, 3 and 5 times per day. The feeding rate was 8% of total body weight per day.The parameters were specific growth rate, average body weight gain, feed conversion ratio, protein retention,lipid retention, protein efficiency ratio and survival rate. The results of experiment indicated that there were significant different(P<0.05) among treatments for specific growth rate, individual body weight gain, feed convertion ratio,protein retention, lipid retention and protein efficiency ratio.The highest value for specific growth rate (7.03%) and protein retention (54.59%) were found for feeding frequency 5 times per day.The values of feed conversion ratio and survival rate for feeding frequency 5 times per day were 0.83 and 100%, respectively.